Examining the digital disparities among adolescents in rural Western Kenya - Odhiambo, Evelyn Achieng (Rhodes University, 2026)
In Kenya, widows’ children living in resource-poor and rural locations remain one of the demographics facing limited access to digital technology, as well as other social and economic needs. This study assessed the access to and use of technology among widows’ children in the Lake Victoria Region in Kisumu, Kenya. It explored access, opportunities, and challenges of navigating technology in everyday life among widows’ children, thus creating a basis for improving and promoting children’s socio-educational outcomes in the digital age. To thoroughly examine the extent to which these inequalities were prevalent among widows’ children, this study utilised Van Dijk's (2005) theory of Resource and Appropriation which argues that the digital divide is a personal, positional and background inequality. The study employed a quantitative methodology, using semi-structured survey questionnaires and a case study design to study children of widows in rural Kenya, aged 13-18 years and randomly selected using the sampling framework developed in collaboration with Nyanam International. The data were analysed using a descriptive, inferential and thematic analysis method. The findings indicated a significant awareness of communications and information technologies, where 94% of the respondents reported knowing what digital technology was. However, access was either limited or restricted, with only 67% of the 94% who were aware reporting being able to access digital technologies through shared devices. There was also a significant skills gap. These restrictions were reported to be due to poverty, resource-intensive costs, parental restrictions, and respondents' techno-fear. The qualitative data, generated from the open-ended survey questions, demonstrated respondents' desire for more child-friendly, age-appropriate, and safe digital technologies. Notably, the study reported that evidence of socio-cultural factors (widowhood status and stigma interrogated through the lens of financial power) could restrict widows' children's effective use of technology. The study argues that interrogating the digital divide among the differing populations of children, particularly those living in vulnerable and marginalised contexts, offers wider evidence on the importance of technology access and use in improving children's educational outcomes and development in a digital world. One main limitation of the study is that, its findings may not be generalisable to a broader population of children as they are specific to those affected by widowhood.
a study of technology access and usage among children of widows
Keywords: Uncatalogued